2014
DOI: 10.1371/journal.pone.0092996
|View full text |Cite
|
Sign up to set email alerts
|

Modular Hyperthermostable Bacterial Endo-β-1,4-Mannanase: Molecular Shape, Flexibility and Temperature-Dependent Conformational Changes

Abstract: Endo-β-1,4-mannanase from Thermotoga petrophila (TpMan) is a hyperthermostable enzyme that catalyzes the hydrolysis of β-1,4-mannoside linkages in various mannan-containing polysaccharides. A recent study reported that TpMan is composed of a GH5 catalytic domain joined by a linker to a carbohydrate-binding domain. However, at this moment, there is no three-dimensional structure determined for TpMan. Little is known about the conformation of the TpMan as well as the role of the length and flexibility of the lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Some hyperthermostable enzymes produced by this microorganism have demonstrated great potential for industrial applications and served as models to investigate structure-function-stability relationships in glycosyl hydrolases Cota et al 2011;Santos et al 2012;Silva et al 2014). For industrial purposes, an enzyme of thermophilic origin can be considered favorable, since elevated temperatures can yield higher substrate solubility, lower viscosity, and thereby lower pumping costs, and limited risks of bacterial contamination (Lundemo et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some hyperthermostable enzymes produced by this microorganism have demonstrated great potential for industrial applications and served as models to investigate structure-function-stability relationships in glycosyl hydrolases Cota et al 2011;Santos et al 2012;Silva et al 2014). For industrial purposes, an enzyme of thermophilic origin can be considered favorable, since elevated temperatures can yield higher substrate solubility, lower viscosity, and thereby lower pumping costs, and limited risks of bacterial contamination (Lundemo et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…1). In general, high-resolution X-ray crystal structures of the individual modules are fit into the low-resolution SAXS molecular envelopes (~12-20 Å) generating pseudo-atomic resolution models of the ultra multimodular enzymes and their complexes [8][9][10][11]. Determining ultra multimodular protein structures using the combination of XRC and SAXS is an emerging frontier in structural biology research, providing important fundamental insights into full-length CAZymes with industrial, biomedical, and environmental significance.…”
Section: Introductionmentioning
confidence: 99%
“…found that the truncated ThMan5A lacking CBD from Trichoderma harzianum exhibited improved expression efficiency and thermal stability. Furthermore, the linker can optimize the geometry between the other two domains at high temperatures and protect the enzyme , . Therefore, studies relating to enzyme structure can optimize the properties of the enzyme and make it more effective in the catalytic reaction.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 At present, research on -mannanase has mainly focused on gene cloning, expression, characterization, production and structural analysis. 13,14 Da Silva et al 15 found that endo--1,4-mannanase was composed of a GH5 catalytic domain connected by a linker to a carbohydrate-binding domain (CBD). The function and mechanism of each domain of mannanase was different, with different origins.…”
Section: Introductionmentioning
confidence: 99%